Age Determination by Medial End of Clavicle- Radiological Study - Makaju, Sarbada; Karmacharya, Menuka; Chaudhary, Sonam (Journal of College of Medical Sciences-Nepal, 2021)
Introduction The clavicle was a modified long bone and it is placed horizontally. Anatomically, clavicle consist of medial and lateral end. It doesn’t consist of medullar cavity. The medial epiphysis was the last epiphysis of the body to fuse at the age of 25-28 years of age. Methods The study was conducted on 369 chest X-ray of a patient from Department of Radiology, Duwakot, Kathmandu between September-November 2020 after getting the ethical clearance from the Institutional Review Committee (reference no. KMC-IRC 2003202005). The Convenient sampling was done. The stages of ossification of the medial epiphysis of clavicle were studied. The data was analysed with Statistical Package for the Social Sciences 20 version. Results Total sample size was 369. Out of that 208(56.4%) were Male and 161(43.6%). The stages of the ossification begin at the age of 15 in Male and 12 in Female. In the both gender, the medial epiphysis completed its ossification the Stages 5 at the age of 26. The right and left side of clavicle start its ossification at the same age group and completed also in same age. Conclusions The ossification of the medial epiphysis of right and left side of clavicle begins and end at same time. In both the gender, the stages 5 completed at age of 26. This showed that the clavicle fused completely at the age of 26.